Effect of Semen Leaching and Soybean Lecithin Levels in Tris Extenders on the Quality of Preserved Sheep Spermatozoa at 5oC Temperature - Salmin Salmin; Marsudi Marsudi; Deka Uli Fahrodi; Hendro Sukoco (CV. Rayyan Dwi Bharata, 2022)
This study aims to study the leaching of semen and the level of soy bean lecithin (Soybean lecithin) in relation to the quality of sheep spermatozoa preserved at 5OC. The study used a Complete Randomized Design (RAL) factorial pattern of 2 x 5 x 3. As the first factor is cement washing (P), consisting of P0 = Fresh cement without washing and P1 = Fresh cement undergoes a washing process. The second factor is the level of soy bean lecithin (L), consisting of L0, L1, L2, L3, and L4. Independent variables are cement washing (P) and soybean lasitin levels (L). As a dependent variable is the quality of spermatozoa at a storage temperature of 5⁰C, which consists of progressive motility, viability, abnormality and intergrity of the spermatozoa membrane. The results of the study obtained that the treatment of cement leaching and soy bean lecithin levels together did not show any noticeable interaction, however, single-seeded lecithin levels showed markedly different influences (P≤0.05) and the washing treatment showed no noticeably different influence on all quality parameters of sheep spermatozoa during five days of storage at 5⁰C. The use of soy bean lecithin as a component of sheep cement extenders is effective against samples of unwashed cement or washed cement. The best quality of sheep spermatozoa was obtained at the treatment of 3% soy bean lecithin levels in Tris extenders against washed and unwashed semen preserved for five days of storage at 5oC with an average progressive motility percentage of 63.18%; viability 72.20%; abnormality 12.43%; and membrane integrity of 72.92%.